2003
DOI: 10.1046/j.1525-1594.2003.07131.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Prepare Multicellular Spheroids in Cancer Cell Lines Using a Thermo‐Reversible Gelation Polymer

Abstract: The purpose of this study is to utilize the thermo-reversible gelation polymer in which the sol-gel transitting phase is reversibly changed by temperature in a three-dimensional culture system. Human cancer cells have been observed to form multicellular spheroids, whereas fibroblasts slowly develop into small spheroids with the culture medium including this polymer. This polymer has some advantages for use as a culture material, as follows: first, cancer cells grow three-dimensionally in the aqueous solution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The present method has the following advantages: (1) it enables cultivation of progenitor/stem cells as a single cell clone from the primary culture, (2) it is simple and easy without a need for any sophisticated apparatus such as a cell sorter, (3) it enables simple recovery of colonies by reducing the temperature, and (4) it can be used for isolation of stem cells other than skin stem cells, for example, neural stem cells and bone marrow mesenchymal stem cells (manuscript in preparation). Since the polymer is biologically inert, cells that formed colonies in the gel apparently grew anchorage-independently [Tsukikawa et al, 2003]. This is in accordance with results of previous studies in which stem cells from nervous tissues [Weiss et al, 1996;Uchida et al, 2000] and mammary glands [Dontu et al, 2003] were isolated by cultivating the cells in a suspension.…”
Section: Discussionsupporting
confidence: 90%
“…The present method has the following advantages: (1) it enables cultivation of progenitor/stem cells as a single cell clone from the primary culture, (2) it is simple and easy without a need for any sophisticated apparatus such as a cell sorter, (3) it enables simple recovery of colonies by reducing the temperature, and (4) it can be used for isolation of stem cells other than skin stem cells, for example, neural stem cells and bone marrow mesenchymal stem cells (manuscript in preparation). Since the polymer is biologically inert, cells that formed colonies in the gel apparently grew anchorage-independently [Tsukikawa et al, 2003]. This is in accordance with results of previous studies in which stem cells from nervous tissues [Weiss et al, 1996;Uchida et al, 2000] and mammary glands [Dontu et al, 2003] were isolated by cultivating the cells in a suspension.…”
Section: Discussionsupporting
confidence: 90%
“…It has been experimentally used as an artificial pancreas, cell culture and wound-dressing material in the treatment of skin defects, and has been proven effective [4][5][6]. We have developed a new procedure for treatment of liver injuries using TGP.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach involves the use of hybrid polymers composed of biomacromolecules grafted with PNIPAM. For example, our previous studies showed that PNIPAM-grafted gelatin and PNIPAM-grafted hyaluronan, which are prepared by photochemically driven quasi-living graft polymerization initiated from the dithiocarbamate group derivatized on biomacromolecules, which proceeds reproducibly under well-defined polymerization condition, exhibit thermo-reversible phase transformation, resulting in temperature-dependent cell adhesion/ detachment on their coated surfaces and cell inoculation in gel [9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, as the temperature is increased above the LCST, the polymer precipitates from the aqueous solution due to hydrophobic associations. PNIPAM and its copolymers have been widely utililized as thermoresponsive drug delivery vehicles [7,8], threedimensional (3D) ECMs [9][10][11][12][13][14][15][16][17], tissue-detachable-culture substrates [16] and wound-healing materials [13].…”
Section: Introductionmentioning
confidence: 99%